Recovery and preservation of phenols from olive waste in ethanolic extracts - Galanakis, Charis M.; Tornberg, Eva; Gekas, Vassilis (My University, 2010)
BACKGROUND: The current trend of upgrading undervalued agricultural by-products involves the recovery of natural antioxidants. The purpose of this study was to recover phenols from fresh olive mill wastewater (OMW) with their dispersion in 85 mL ethanol per 100 mL and to investigate the effect of processing parameters on the phenol content and antioxidant capacity of the extracts. Moreover, all these characteristics were monitored over a period of 18 weeks in order to examine their preservation inside the ethanolic medium. RESULTS: Extraction time (30-120 min) was not critical for the process, while a pre-treatment step with the addition of ethanol in lower concentrations (20 mL per 100 mL or less) seems to affect negatively the recovery of the phenols in the final (85 mL per 100 mL) ethanolic medium. A pre-heating step of OMW at 50-60 degrees C as well as 80 degrees C resulted in reduction of the phenol concentrations and antioxidant activities of the extracts, probably due to the generation of enzymatic and non-enzymatic reactions, respectively. Nevertheless, extracts from the heat treated samples generally preserved their phenol characteristics as well as ferric ions reduction ability and indeed increased their radical scavenging activity during storage. CONCLUSION: Extraction of the phenols was mainly governed by their solubilization in the hydro-ethanolic mixture as well as the thermal pre-treatment of OMW. Results can be utilized to optimize the recovery and preservation of phenols from OMW in hydro-ethanolic mixtures. (C) 2010 Society of Chemical Industry
Keywords: Antioxidant properties; Extraction; Olive mill wastewater; Phenol; Solubilization